School refusal: mapping the literature by bibliometric analysis - Ulaş, Sümeyye; Gonzálvez, Carolina; Seçer, İsmail (Frontiers in Psychology, 2024)
School refusal is considered a risk factor for academic, social, and personal situations, such as school dropouts. Studies have been carried out on school refusal for almost 50 years. However, general research trends have not been mapped yet. This study summarizes the bibliometric analysis of scientific collaborations and prevalence across locations by country and institution, leading researchers, journals, and trends (keywords) in school refusal research. The United States, Japan, Spain, and England are the countries that stand out in terms of school refusal. It can be said that the Journal of American Academy of Child and Adolescent Psychiatry, Cognitive and Behavioral Practice, and Frontiers in Psychology are important journals that publish on school refusal. Researchers named Christopher A. Kearney, Carolina Gonzálvez, Jose Manuel Garcia-Fernandez, David A. Heyne, and Brigit M. Van Widenfelt have been found to have more intensive studies and collaborations on school refusal. The authors keywords common use for school refusal; are truancy, school absenteeism, adolescence, school attendance, school phobia, autism spectrum disorder, and bullying. The findings show that school refusal is a current research area, and scientific collaborations continue to be established. The findings reveal all the details of the school refusal research.